Virus and virus-like diseases of citrus in Turkey - Yilmaz M. (Proceedings of the Mediterranean network on certification of citrus. 1995-1997, 1998)
More than 15 virus and virus-like diseases were detected in Turkish citrus groves among which psorosis complex, stubborn, cachexia, exocortis, infectious variegation, concave gum, impietratura, cristacortis, satsuma dwarf, gummy bark and woody gall. Tristeza is present in a mild form and apparently it is not vector-transmitted in the field. A new disease transmitted by Parabemisia myricae has been reported, which is very similar to citrus infectious variegation.
Round Table on: Citrus Virus and Virus-like Diseases and Certification: State of the Art, 1995/07/21, Bari (Italy)